Effectiveness of Turmeric Ethanol Extract Cream Preparation (Curcuma Longa) in Speeding up Wound Healing in Male Wistar Rats - Wang Ling; Florenly Florenly; Liena Liena; Dewi Riastawaty Purba (Budapest International Research and Critics University, 2022)
Injury is the loss or damage of some body tissues, due to a factor that interferes with the body's protective system. The results of several studies state turmeric rhizome extract is effective in wound healing. This study aims to find out the effect of turmeric extract (Curcuma longa) on wound healing in white rats. This type of research is experimental with the approach of Pre-test and Post-test group only control design, conducted November to December 2020. The samples used were turmeric rhizomes (Curcuma Longa) and male white rats. Determination of the size of the sample according to Federer's formula, so that the number of samples as many as 25 mice, the division of 4 treatment groups and 1 control group. The results of the study from the Anova test obtained a Sig value. Calculate 0.000 while sig value (α) is 0.05 which means sig value. Count sig < (α). This means that there is a real influence of the administration of turmeric extract (Curcuma Longa) on the healing of sores in mice. Turmeric ethanol extract (Curcuma Longa) has several bioactive compounds such as alkaloids, flavonoids, saponins, and tannins that play a role in wound healing. The optimum concentration of turmeric ethanol extract (Curcuma Longa) that can cure sores in white rats is 5%. The highest percentage of cures on k-14 days was in the positive control (Bioplacenton®) which was 95% and followed by extract 5% v/ v with a cure percentage of 90%. The creamy preparation of turmeric ethanol extract (Curcuma Longa) has an ability that is close to Bioplacenton® in healing wounds in mice.